Stability implications of bulk power networks with large scale PVs. (15th November 2019) - Kumar, Dhivya Sampath; Sharma, Anurag; Srinivasan, Dipti; Reindl, Thomas
Abstract: With the shift in renewable portfolio standards, conventional fossil-fuel based generators are expected to be partially or fully replaced with renewable energy sources such as photovoltaics (PVs). However, replacing the conventional synchronous generators with PV generators may raise new stability concerns such as lack of inertia, insufficient reactive power and voltage fluctuations, which can jeopardize the reliability of the entire network. In this paper, various impacts of integrating utility-scale PVs and rooftop PVs and replacing the existing conventional generators on the stability of a power network are investigated. Detailed steady state, transient and small signal analyses are conducted on a large test system, namely Texas 2000-bus system for different PV penetration levels. System transients such as line faults, double-line faults, loss of generator, loss of PVs and cloud cover scenarios are simulated to study their impacts on the test system with different PV penetration levels. It is demonstrated from the impact analysis that the benefits of PVs are highly dependent on a spectrum of factors such as node criticality, type, location and penetration of PVs, and type of transients. Furthermore, the influence of battery energy storage system that are generally associated with PVs on the system stability is also discussed. Highlights: Modeling and analysis of power network with different solar penetration levels. Voltage stability analysis of grid with solar determine the most sensitive buses. Transient and small-signal stability analysis to analyze the impacts of solar. Analysis with storage devices to determine their influence in network damping.